Endocardial Fibroelastosis is Secondary to Hemodynamic Alterations in the Chick Embryonic Model of Hypoplastic Left Heart Syndrome - Pesevski, Zivorad; Kvasilova, Alena; Stopkova, Tereza; Nanka, Ondrej; Drobna Krejci, Eliska; Buffinton, Christine; Kockova, Radka; Eckhardt, Adam; Sedmera, David (Developmental dynamics, 2018)
BACKGROUND: Endocardial fibroelastosis (EFE) is a diffuse thickening of the ventricular endocardium, causing myocardial dysfunction and presenting as unexplained heart failure in infants and children. One of the postulated causes is persistent and increased wall tension in the ventricles. RESULTS: To examine whether reduced ventricular pressure in a chick model of hypoplastic left heart syndrome (HLHS) induced by left atrial ligation (LAL) at embryonic day (ED) 4 is associated with EFE at later stages, myocardial fibrosis was evaluated by histology and immunoconfocal microscopy and mass spectrometry (MS) at ED12. Immunohistochemistry with collagen I antibody clearly showed a significant thickening of the layer of subendocardial fibrous tissue in LAL hearts, and MS proved this significant increase of collagen I. To provide further insight into pathogenesis of this increased fibroproduction, hypoxyprobe staining revealed an increased extent of hypoxic regions, normally limited to the interventricular septum, in the ventricular myocardium of LAL hearts at ED8. CONCLUSIONS: Abnormal hemodynamic loading during heart development leads to myocardial hypoxia, stimulating collagen production in the subendocardium. Therefore, EFE in this chick embryonic model of HLHS appears to be a secondary effect of abnormal hemodynamics. Developmental Dynamics 247:509-520, 2018. © 2017 Wiley Periodicals, Inc.
Keywords: endokard; srdce; chick embryo; Hypoxia; Hypoplastic Left Heart Syndrome; kolagen; Endocardium; Hemodynamics; syndrom hypoplazie levého srdce; collagen; Animals; kuřecí embryo; zvířata; Collagen; HLHS; Endocardial Fibroelastosis; left atrial ligation; hemodynamika; Heart; endokardiální fibroelastóza; Chick Embryo